A Semantic Analysis of Figurative Meaning in the Song “Photograph” by Ed Sheeran - Enzelly Hernita Sidabalok; Bernieke Anggita Ristia Damanik (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines figurative meaning in the lyrics of Photograph by Ed Sheeran through a semantic and textual analysis approach. The research employed a non-empirical qualitative design grounded in library-based interpretation using the official song lyrics as the primary data source. The analysis focused on metaphorical, symbolic, hyperbolic, and contextual expressions interpreted through semantic theories proposed by Leech and Lyons. The findings indicate that figurative language in the song functions as an integrated semantic system for representing emotional memory, intimacy, longing, and relational permanence. Denotative and connotative meanings interact dynamically to construct emotional depth while maintaining lexical accessibility. Contextual semantics also strengthens interpretation because emotional meaning emerges through thematic continuity, situational imagination, and symbolic association rather than isolated lexical forms. Expressions related to photographs, frozen time, and emotional return create psychologically resonant imagery that intensifies listener engagement. The study confirms that contemporary song lyrics operate as literary discourse capable of encoding complex emotional experiences through semantically layered yet linguistically simple expressions.